Identificación y elaboración de productos turísticos para el cantón Sigchos. - Sabando Cachago, Diego Alexander (2023)
Sigchos has potential for tourism, for its natural and cultural areas, in addition to its proximity to Quilotoa makes it an ideal place for the implementation of tourist activities, which is why the need to develop a tourist product in the canton, is evident. depending on its characteristics. To develop the project, key actors were selected to obtain information and through a field trip the authorities were interviewed (Mayor and tourism boss) additionally, surveys were carried out to residents in order to know the existence of tourist elements and the services provided in the town (within them tourism service providers); tourists were also surveyed to know the activities they developed in the canton and their experience when performing them. With the information obtained verified with the bibliographic collection, we proceeded to validate the inventory of existing tourist attractions using a Check list, with a total of 88 attractions bibliographically described, which with the field exit were 69 validated and 2 were added (inventoried with the MINTUR files); obtaining a database of 71 attractions (48 natural and 23 cultural). For the design of the tourist product was followed the methodology of the Planning Manual of Tourism Products, which consists of the analysis of the destination that found that it has deficiencies such as lack of tourist infrastructure, limited accessibility to certain attractions, lack of transport, and there are no basic services in the attractions. It was determined the profile of the tourist who is mainly foreign and the type of tourism that makes is nature and adventure. With the background presented, 2 routes were designed, with a duration of 2 days – 1 night, and a full day; activities such as hiking, cycling, abseiling and photography are proposed; with an all-inclusive service (transport, food, local guide and accommodation). Finally, a SWOT analysis was carried out, at the external level the need to innovate in tourism products and expand the market to increase the number of tourists is evidenced, because it has a wide range of natural and cultural resources, which can strengthen adventure tourism. As strategies, it is considered to motivate the community through talks to improve the quality of the service, and to use digital and innovative means for the promotion of the attractions and the existing products, including the routes of this project. In conclusion, there is the possibility of developing new tourism products and analyzing the tourism market in depth for this, it is important to focus joint efforts between authorities, residents and other tourism actors, to promote the attractions and activities that are developed in the canton.